Про взаємодію елементарних зарядів з електричним стаціонарним полем - Придубков, П.Я.; Хоменко, І.В. (Електротехніка і електромеханіка, 2011)
The interaction between a stationary electric charges as well as elementary currents describe the interaction of charged particles and a stationary electric field in accordance with the principle of least action with the Lagrangian, analytical dependences describing the interaction of elementary charges with the electric stationary field.